Ultrafast Coulomb explosion of a diiodomethane molecule induced by an X-ray free-electron laser pulse. Issue 30 (22nd May 2017) - Takanashi, Tsukasa; Nakamura, Kosuke; Kukk, Edwin; Motomura, Koji; Fukuzawa, Hironobu; Nagaya, Kiyonobu; Wada, Shin-ichi; Kumagai, Yoshiaki; Iablonskyi, Denys; Ito, Yuta; Sakakibara, Yuta; You, Daehyun; et al.
Abstract : The Coulomb explosion mechanism of a CH2 I2 molecule is rather different to that of CH3 I. The kinetic energy of iodine ions is ∼3 times larger due to Coulomb repulsion of the two iodine ions, while that of carbon ions is almost the same for both, as indicated by the red arrows that represent kinetic energies of the atomic ions. Abstract : Coulomb explosion of diiodomethane CH2 I2 molecules irradiated by ultrashort and intense X-ray pulses from SACLA, the Japanese X-ray free electron laser facility, was investigated by multi-ion coincidence measurements and self-consistent charge density-functional-based tight-binding (SCC-DFTB) simulations. The diiodomethane molecule, containing two heavy-atom X-ray absorbing sites, exhibits a rather different charge generation and nuclear motion dynamics compared to iodomethane CH3 I with only a single heavy atom, as studied earlier. We focus on charge creation and distribution in CH2 I2 in comparison to CH3 I. The release of kinetic energy into atomic ion fragments is also studied by comparing SCC-DFTB simulations with the experiment. Compared to earlier simulations, several key enhancements are made, such as the introduction of a bond axis recoil model, where vibrational energy generated during charge creation processes induces only bond stretching or shrinking. We also propose an analytical Coulomb energy partition model to extract the essential mechanism of Coulomb explosion of molecules from the computed and the experimentally measured kinetic energies of fragment atomic ions by partitioning each pair Coulomb interaction energy into two ions of the pair under the constraint of momentum conservation. Effective internuclear distances assigned to individual fragment ions at the critical moment of the Coulomb explosion are then estimated from the average kinetic energies of the ions. We demonstrate, with good agreement between the experiment and the SCC-DFTB simulation, how the more heavily charged iodine fragments and their interplay define the characteristic features of the Coulomb explosion of CH2 I2 . The present study also confirms earlier findings concerning the magnitude of bond elongation in the ultrashort X-ray pulse duration, showing that structural damage to all but C–H bonds does not develop to a noticeable degree in the pulse length of ∼10 fs.